Moldova : Health Transformation Program - World Bank (Washington, DC, 2014)
The proposed Health Transformation Program objective is to reduce key risks for non-communicable diseases, improve financial protection and enhance efficiency of health services in Moldova. The proposed four-year (2014-2018) Health Transformation Program will support a subset of the Strategy s first three sections. The proposed Program-for-Results (PforR) covers a time slice of a portion of the GOM program. It is expected to contribute to the Government program and, therefore, health system as a whole, by disbursing funds against achievement of a subset of its key results.